Methods that matter : integrating mixed methods for more effective social science research - Hay, M. Cameron, 1965- (The University of Chicago Press, 2016)
To do research that really makes a difference - the authors of this book argue - social scientists need questions and methods that reflect the complexity of the world. Bringing together a consortium of voices across a variety of fields, this title provides successful examples of mixed methods research that do just that.